2002
DOI: 10.1007/s00280-002-0454-2
|View full text |Cite
|
Sign up to set email alerts
|

Urinary and fecal excretion of topotecan in patients with malignant solid tumours

Abstract: Fecal and urinary excretion of unchanged topotecan were the major routes of topotecan elimination. Approximately 28% of the intravenous dose and 43% of the oral dose of topotecan were unaccounted for and eliminated through other routes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
19
0

Year Published

2004
2004
2013
2013

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(19 citation statements)
references
References 18 publications
0
19
0
Order By: Relevance
“…In patients with normal renal function, topotecan is mainly eliminated by renal excretion, with approximately half of the administered intravenous dose excreted as parent drug in the urine [10]. Recently, pharmacokinetic studies in patients with impaired renal function showed that reduction of topotecan dosages in patients from 1.5 to 0.75 mg/m 2 resulted in adequate topotecan levels [11].…”
Section: Discussionmentioning
confidence: 99%
“…In patients with normal renal function, topotecan is mainly eliminated by renal excretion, with approximately half of the administered intravenous dose excreted as parent drug in the urine [10]. Recently, pharmacokinetic studies in patients with impaired renal function showed that reduction of topotecan dosages in patients from 1.5 to 0.75 mg/m 2 resulted in adequate topotecan levels [11].…”
Section: Discussionmentioning
confidence: 99%
“…in cancer patients (Herben et al, 2002). Although topotecan undergoes both renal and hepatobiliary excretion (Stewart et al, 1994;Furman et al, 1996), it has been shown to undergo only limited metabolism (Herben et al, , 2002Rosing et al, 1997). A population pharmacokinetic analysis indicated that tubular secretion in addition to glomerular filtration is involved in topotecan renal clearance in humans (Mould et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…Topotecan is primarily excreted into urine as both lactone and hydroxyl acid forms, accounting for approximately 49% of the dose administered i.v. in cancer patients (Herben et al, 2002). Although topotecan undergoes both renal and hepatobiliary excretion (Stewart et al, 1994;Furman et al, 1996), it has been shown to undergo only limited metabolism (Herben et al, , 2002Rosing et al, 1997).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations